Alterations of the cyclin D1/p16-pRB pathway in mantle cell lymphoma - Dreyling, Martin; Bullinger, Lars; Ott, German; Stilgenbauer, Stephan; Müller-Hermelink, Hans K.; Bentz, Martin; Hiddemann, Wolfgang; Döhner, Hartmut (Cancer research, 1997)
Mantle cell lymphoma (MCL) has recently become generally accepted as a subentity of malignant lymphomas that is characterized by the chromosomal translocation t(11;14)(q13;q32), resulting in the overexpression of cyclin D1. Cyclin D1 forms a complex with cell cycle-dependent kinase (cdk) 4, which inactivates the retinoblastoma protein (pRB) via phosphorylation. However, in transgenic mice, the overexpression of cyclin D1 alone is not sufficient for the development of malignant lymphoma. To determine whether other members of the pRB pathway contribute to the malignant transformation of MCL, we analyzed 37 cases of MCL that were well characterized by morphology, immunophenotype, and/or interphase cytogenetics [detection of t(11;14)(q13;q32)]. Interphase fluorescence in situ hybridization was performed using a cosmid contig (250 kb) of the CDKN2/p16 region (encoding an inhibitor of the cyclin D1/cdk4 complex) and a phage contig (200 kb) of the Rb region. CDKN2/p16 deletion was detected in 15 cases (41%), including 6 homozygous deletions; Rb was deleted in 15 cases (41%), all of which were hemizygous deletions. Nine cases (24%) had deletions of both CDKN2/p16 and Rb. Further analysis of a subset of 17 MCLs revealed a highly significant correlation between CDKN2/p16 deletion and proliferation index, determined by the rate of Ki67 expression (P = 0.014; t test). No significant correlation was found between CDKN2/p16 deletion and the blastoid variant of MCL (P = 0.23; Fisher's test) or between proliferation index and blastoid morphology (P = 0.51; t test). Deletion of Rb did not have any impact on cell proliferation in addition to CDKN2/p16 deletion (P = 0.76; t test). Additional analysis of 13q14 deletions suggests that these deletions may target another gene telomeric to Rb. We conclude that deletion of CDKN2/p16 occurs in approximately one-half of MCLs and is a more relevant indicator of the proliferative features as compared to morphological criteria. In contrast, although deletions of chromosomal band 13q14 are frequent in MCL, inactivation of Rb seems not to be involved in the pathogenesis of MCL.
Gesehen am 03.04.2024